2014
DOI: 10.1080/01916122.2014.892906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonality and time after anthesis on the viability and longevity ofCannabis sativapollen

Abstract: The aim of this study was to evaluate the pollen viability and longevity of Cannabis sativa, which is a significant economic crop. Viability and longevity are evaluated using different staining techniques: Alexander's, Triphenyl Tetrazolium Chloride (TCT) and Fluorochromatic Reaction (FCR). The results of this study show that FCR is the most reliable and accurate for assessing viability and longevity in C. sativa. Viability was measured over days and across 2010. Viability was greatest between 0 -3 days of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…As a result of a week-long cold pretreatment applied directly on excised buds prior to microspore culture, a stress-derived slight decrease in microspore viability was detected. Our findings are in agreement with results published by Choudhary et al (2014) , who studied how pollen viability was significantly influenced by seasonal fluctuations in temperature and humidity. Researchers reported a significant decrease of pollen viability at low temperatures, reaching the lowest viability rates in the winter season.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result of a week-long cold pretreatment applied directly on excised buds prior to microspore culture, a stress-derived slight decrease in microspore viability was detected. Our findings are in agreement with results published by Choudhary et al (2014) , who studied how pollen viability was significantly influenced by seasonal fluctuations in temperature and humidity. Researchers reported a significant decrease of pollen viability at low temperatures, reaching the lowest viability rates in the winter season.…”
Section: Discussionsupporting
confidence: 93%
“…The great amount of microspores and pollen grains produced in each flower bud (>150,000), together with the high rates of microspore viability reached for all phenotypes (>50%), makes C. sativa a suitable system able to provide, in a very quick period of time (≈30 days after seed germination), huge populations of viable vacuolate microspores and young bi-cellular pollen grains potentially inducible to afford microspore and pollen embryogenesis experiments. Viability rates obtained in our research are similar to the ones reported by Choudhary et al (2014) which, depending on the season, oscillated among 33.3 and 83.0%, while in another work (Zottini et al, 1997) a viability rate for mature pollen grains of 92% was reported. This difference among viability rates could be attributable to the microspore isolation procedure, as viability measurements in the former works were performed on mature pollen grains naturally released after anthesis.…”
Section: Cannabis Sativa Is a Suitable Candidate For Androgenesis Experiments Mainly Due To Its Fast Production Of Viable And Potentiallysupporting
confidence: 89%
“…A.M.U/31337 (male), 31338 (female)/2010 were deposited in Botany Department, Aligarh Muslim University, Aligarh for future reference. Monthly mean maximum and mean minimum temperature and relative humidity were selected for this study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pollen viability was examined using fluorescein diacetate (FDA) and pollen germination (Heslop‐Harrison and Heslop‐Harrison, ; Djanaguiraman et al., ; Choudhary et al., ). Pollen enzyme activity was assessed by performing a fluorochromatic reaction with 0.05 mg mL −1 FDA which enters the pollen wall and is hydrolyzed by esterase (Choudhary et al., ). Mature, non‐dehisced anthers were removed from three buds per plant, stained in FDA, and observed under a fluorescent microscope with a fluorescein isothiocyanate (FITC) filter.…”
Section: Methodsmentioning
confidence: 99%